Availability and Use of Learning Resources for Basic School Mathematics Instruction in Ghana - Edward Abatanie Padmore; Ibrahim Mohammed Gunu; Clement Ayarebilla Ali (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
The study investigated the availability and use of mathematics learning resources at the basic school levels. Ascertaining the availability, use, and mathematics learning resources were the epicenters of this study. The methodology employed was the descriptive survey research design. Through the census technique, 102 junior high school mathematics facilitators participated in the study. The data collection instrument was the questionnaire. Experts and two lecturers validated the instruments using appropriate design, sampling techniques, and data collection tools. The repetitions of the same participants for four different research questions also yielded a 0.80 reliability coefficient. The researchers used frequency and percentage to analyze the data. The results showed that attribute blocks, base ten blocks, and geoboards were the worst unavailable resources. Also, even though facilitators were involved in improvising a few resources, most were not improvised. Lastly, the major challenges were curriculum content, textbooks, and school funds, making many mathematics learning resources nonimprovisable. It was therefore recommended that practical courses in mathematics learning resources construction and usage be incorporated into teacher training and regular professional training and retraining programs.